Academics writing : the dynamics of knowledge creation /: the dynamics of knowledge creation. (2019) - Tusting, Karin, 1973-; McCulloch, Sharon; Bhatt, Ibrar; Hamilton, Mary, 1949-; Barton, David, 1949-
No abstract available